Analysis of Production Process Performance Using Computer - Pawlak, Szymon; Fornalczyk, Agnieszka (Management systems in production engineering, 2025)
Planning a production process in terms of correctly defining its efficiency, duration and the level of generated costs is a difficult task. Manufacturing processes are characterized by a high level of complexity and are exposed to a large number of external factors that are difficult to predict. In many cases, one of the tools supporting decisions in the analysis of manufacturing process parameters is the use of computer simulation both at the process planning stage and in real time during its implementation. In this article, a computer simulation tool (FlexSim simulation software) was used to analyze the parameters of a selected production process. The conducted analyses allowed for indicating the direction of actions in the use of computer simulation as a decision support tool at selected stages of production process planning in the area of evaluating solutions aimed at implementing improvements.